The Inverting Pyramid : Pension Systems Facing Demographic Challenges in Europe and Central Asia. - Schwarz, Anita M. (Europe and Central Asia reports., 1905)
Europe's pension systems -among the most celebrated features of its social welfare model- face tremendous challenges. With only 11 percent of the world's population, Europe spends about 60 percent of global outlays on social protection, largely in pensions. In many countries, pension rules have encouraged people to retire sooner, while enjoying longer lives. Payroll taxes on a continuously expanding contributory base have financed these benefits. This model of pension provision is now being severely tested as pension systems reach maturity, while the population is aging and the labor force is.